A Novel Modified Switched Inductor Boost Converter With Reduced Switch Voltage Stress - Shima Sadaf (16875999) (2021)
Recently, switched inductor (SI) and switched capacitor techniques in dc-dc converter are recommended to achieve high voltage by using the principle of parallel charging and series discharging of reactive elements. It is noteworthy that four diodes, one high-voltage rating switch, and two inductors are required to design classical SI boost converter (SIBC). Moreover, in classical SIBC, the switch voltage stress is equal to the output voltage. In this article, modified SIBC (mSIBC) is proposed with reduced voltage stress across active switches. The proposed mSIBC configuration in this article is transformerless and simply derived by replacing the one diode of the classical SI structure with an active switch. As a result, mSIBC required low-voltage rating active switches, since the total output voltage is shared into two active switches. Moreover, the proposed mSIBC is low in cost, provides higher efficiency, and requires the same number of components compared with the classical SIBC. The continuous conduction mode and discontinuous conduction mode analysis, the effect of nonidealities on voltage gain, design methodology, and comparison are presented in detail. The operation and performance of the designed 500-W mSIBC are experimentally validated under different perturbations. Other Information Published in: IEEE Transactions on Industrial Electronics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/tie.2020.2970648